Does auditor religiosity moderate the effect of auditor expertise on audit quality? - Anwar, Achmad Syaiful Hidayat; Ardianto, Ardianto (Journal of Accounting and Investment, 2025)
Research aims: This study examines the role of religiosity in the relationship between auditor expertise and audit quality.Design/Methodology/Approach: This research employs a survey design with a census study approach. The research sample consisted of 288 audit firm leaders in Indonesia. Hypothesis testing was carried out using SEM-AMOS.Research findings: The analysis results revealed that auditor religiosity moderates the relationship between auditor expertise and audit quality. Religiosity motivates auditors to utilize their expertise optimally, conduct audits more responsibly, objectively, and independently, thereby preventing fraudulent behavior and ensuring the achievement of quality audits.Theoretical contribution/Originality: This study is the first to examine the role of audit religiosity as a moderator in the relationship between auditor expertise and audit quality. The selection of audit religiosity as a moderating variable is based on the inconsistency of previous audit quality literature and the finding that the accounting profession is becoming increasingly secular.Practitioner/Policy implication: This research extends the RBV theory and insights into the significance of auditor religiosity within the broader audit process. This research also helps audit leaders to develop auditor expertise to support quality audits.Research limitation/Implication: Further research is recommended to explore other variables that may influence audit quality. These variables could be explored in relation to factors such as gender, region, culture, age, education level, or ethnicity. The goal is to expand or enrich research findings related to various aspects that determine audit quality.